Diagnostics algorithm of late complications after total correction of Fallot tetralogy and indications to redo surgical operations - Goryachev, A. G.; Dykuha, S. O.; Naumova, L. R.; Atamanyuk, M. Y.; Pischurin, O. A.; Karimov, O.; Iakubiuk, S. O.; Dyadyun, D. M. (Ukrainian Journal of Cardiovascular Surgery, 2016)
427 patients were systematically studied in terms from 10 to 56 years after total correction of Fallot tetralogy. Residual and acquired cardiac pathology was detected in 234 (54%) out of 427 studied patients. Working classification of complications was created: incomplete correction of the lesion (46,2%); RV dysfunction, which developed as the result of pulmonary regurgitation (21,7%); heart valves lesions of iatrogenic and of infections origin (14,9%); complications caused by natural course of the disease or by earlier performed palliative or total correction operations (17,0%). Experience and analysis of 65 redo operations in 62 patients after total correction of Fallot tetralogy in the remote period of observation during the period from 1981 up to 2014 year. Hospital mortality composed 8%. Good and satisfactory remote results were detected in the majority of reoperated patients (79,18%). In all discharged patients a positive dynamics of volumetric and of functional indices of the right and of the left heart ventricles were noted.